African Leadership and Tenure Elongation: Implications for Democracy and Development in Africa (Global Journal of Human-Social Science, 2022)
This work examines the sit-tight syndrome of African leaders who have no respect for the national constitution preferring to remain in power indefinitely despite tenure limitations by the constitution The study adopted leadership theory as its theoretical framework and findings show that probe for wrongdoings the misconception of democracy for the monarchy strong authoritarian instinct lack of accountability and transparency cheap access to state resources and intolerance of opposition are some of the causes of tenure elongation in Africa which has spelt negative implications for democracy and development The work recommends the building of a strong institution independent of the judiciary respect for the rule of law and constitution establishment of constitutional courts in AU to regulate tenure common language and common market establishment